National and subnational trends in obesity prevalence in Iran: a Spatiotemporal study with future predictions - Maryam Shirvani Shiri; Hassan Karami; Amin Ghanbarnezhad; Najmeh Bordbar; Ali Mouseli; Sara Emamgholipour (Scientific Reports)
Abstract Obesity, defined as having a Body Mass Index (BMI) of 30 kg/m² or above, has emerged as a major public health challenge worldwide, and Iran is no exception. This study aimed to examine the socioeconomic and behavioral factors associated with obesity prevalence in Iran by gender from 2006 to 2019, and predict future trends at both national and subnational levels up to 2040. Obesity rates from 31 provinces in Iran between 2006 and 2019 were obtained from the Iran Statistical Yearbook. Spatio-temporal modeling was applied to assess gender-specific factors influencing obesity at the provincial level. Predictions for future obesity trends were generated using spatiotemporal forecasting techniques. Female obesity was significantly associated with divorce (β = 0.239), urbanization (β = 0.035), internet usage (β = 0.040), Log GDP (β = 3.195), and soft drink consumption (β = 0.153). In contrast, male obesity was significantly related to marriage (β = 0.059), divorce (β = 0.124), urbanization (β = 0.012), Log GDP (β = 1.079), soft drink intake (β = 0.002), tobacco usage (β = 0.217), and meat consumption habits (β = 0.030). Spatiotemporal predictions indicate a continued rise in obesity prevalence over the next two decades, with female obesity projected to reach 52.84% by 2040 and male obesity expected to rise to 33.40%. Mazandaran Province is predicted to have the highest obesity rates in 2040, affecting 72.57% of women and 48.21% of men, whereas Sistan and Baluchistan will likely exhibit the lowest obesity prevalence (37.66% in women and 21.43% in men). The findings highlight the urgent need for policy interventions to address the rising prevalence of obesity in Iran. Given the significant socioeconomic and behavioral determinants identified, targeted public health initiatives, lifestyle modifications, and regulatory policies are essential to mitigate the long-term impact of obesity on the healthcare system and overall public health.